Regional Unemployment and Industrial Restructuring in Poland - Andrew Newell; Francesco Pastore (Institute for the Study of Labor (IZA), 2000)
This paper studies regional unemployment inequality in Poland. We find that higher unemployment regions are those experiencing greater change in industrial structure. We also find high unemployment regions are those with higher inflow rates to unemployment rather than longer spells of unemployment. These findings suggest that regional unemployment varies importantly with job destruction in Poland. Econometric analysis of the determinants of employment to unemployment flows reinforces this impression. We use our estimates to assess the extent to which regional unemployment variation is due to economic restructuring. We show that this is cannot be done unambiguously and offer reasons why many previous attempts to separate out the effects of restructuring on unemployment have been unsuccessful
Keywords: J63; P23; 330; Industrial restructuring; unemployment; Polish transition; Regionale Arbeitslosigkeit; Regionaler Arbeitsmarkt; Strukturwandel; Industrieller Strukturwandel; Schätzung; Polen